Komunikasi Antar Budaya Warga Desa Padang Jering Kecamatan Batang Asai, Kabupaten Sarolangun, Jambi - Zulpikal; Zulqarnin; Arfan; Dian Mursyidah; Neneng Hasanah (MAUIZOH: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This research was motivated by the presence of migrants in Padang Jering Village, Sarolagun who demanded that they communicate with local residents. This article will explain the socio-cultural background that influences people's communication practices, and barriers to intercultural communication between local residents and immigrants in Padang Jering Village, as well as finding solutions to these communication barriers. Using qualitative research methods with the type of field research, the study conducted observations and interviews with informants in mid-2020. This study found that cultural elements that influence such as language, religious systems and knowledge. Barriers to intercultural communication between local residents and immigrants are semantic and language barriers. The first attempt to prevent intercultural communication barriers between local residents and immigrants in Padang Jering Village was to use language such as a smile to stay in touch. Second, by using the help of others to become intermediaries to communicate with local residents, including teaching the local language. Third, by using Indonesian when they want to communicate. Researchers reference mutual understanding in culture and other things that have differences, and tolerance in order to communicate smoothly and can avoid barriers to intercultural communication.